2024
DOI: 10.1002/jcsm.13446
|View full text |Cite
|
Sign up to set email alerts
|

Low skeletal muscle mass and treatment outcomes among adults with haematologic malignancies: A systematic review and meta‐analysis

Nadia M. Anabtawi,
Monica Sai Pasala,
Alyssa A. Grimshaw
et al.

Abstract: BackgroundLow skeletal muscle mass (LSMM) and/or, function associated with an increased risk of treatment‐related toxicities and inferior overall survival (OS) among adults with solid malignancies. However, the association between LSMM and treatment‐related toxicities among adults with haematologic malignancies remains unclear.MethodsUsing a pre‐published protocol (CRD42020197814), we searched seven bibliographic databases from inception to 08/2021 for studies reporting the impact of LSMM among adults ≥18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Anabtawi et al recently conducted a meta-analysis of 20 studies encompassing 3468 patients with various hematological malignancies. They found that the presence of low skeletal muscle mass in individuals with cancer was associated with poor progression-free survival, overall survival, and mortality, regardless of the specific type of malignancy [ 27 ]. Our results provide some evidence that associates low muscle mass with adverse survival in MGUS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anabtawi et al recently conducted a meta-analysis of 20 studies encompassing 3468 patients with various hematological malignancies. They found that the presence of low skeletal muscle mass in individuals with cancer was associated with poor progression-free survival, overall survival, and mortality, regardless of the specific type of malignancy [ 27 ]. Our results provide some evidence that associates low muscle mass with adverse survival in MGUS patients.…”
Section: Discussionmentioning
confidence: 99%